African Studies in the Other Europe: A Legitimate Perspective on Africa (Politeja, 2016)
African Studies in the countries that were under communist rule and that today are known as post‑communist, have originally developed an interest in Africa based on ideological, political and economic interests of the state. There has been a gradual shift from ideology to economy while the study of African politics seems to follow the vagaries of the influence that Africa exerts on the world scene. Characteristically, until recently AEGIS did not include a single centre or association based in post‑communist Europe even though in countries such as Poland, Czech Republic and Hungary African studies currently experience considerable growth. This reflects both the hegemony of Western Europe with its strong colonial and neo‑colonial emphases and weak official interest that post‑communist Europe shows for Africa. The article describes changing emphases of eastern European Africanist scholarship and discusses the question of legitimacy of the marginal but non‑colonial approach to African studies. In contradistinction to the Western European African studies and with Eastern European approaches it shows that the latter perspective is useful for a critical look at the hitherto dominant paternalistic style of African studies in Europe.